PENDAMPINGAN PEMBUATAN LEMBAR KERJA SISWA (LKS) BERBASIS KONTEKTUAL LUBUKLINGGAU PADA GURU SEKOLAH DASAR 41 DAN 42 KOTA LUBUKLINGGAU - Idul Adha; Rani Refianti (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
One of the objectives of the mentoring activity is the creation of student worksheets (LKS) on the basis of lubuklinggau based on 41 elementary school teachers and 42 cities of lubuklinggau. In this activity the worksheets that are generated use the city context of Lubklinggau. One reason for choosing the context of the city of Lubuklinggau is that students can understand that learning mathematics can be applied in everyday life. In this dedication activity the teacher has produced questions based on the context of the city of Lubuklinggau which subsequently the questions are arranged in a very simple worksheet format. Besides that, at the end of the activity, a questionnaire was given to respond to the assistance activities carried out. Based on the analysis of the calculation of questionnaire responses obtained a score of 77.58% this shows that the teacher's response to the activities carried out was very good.